2021
DOI: 10.3389/fnut.2021.790697
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Metabolomic Profiling Reveals the Effect of LED Light Quality on Fruit Ripening and Anthocyanin Accumulation in Cabernet Sauvignon Grape

Abstract: Different light qualities have various impacts on the formation of fruit quality. The present study explored the influence of different visible light spectra (red, green, blue, and white) on the formation of quality traits and their metabolic pathways in grape berries. We found that blue light and red light had different effects on the berries. Compared with white light, blue light significantly increased the anthocyanins (malvidin-3-O-glucoside and peonidin-3-O-glucoside), volatile substances (alcohols and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Therefore, adding of anthocyanin did not impact ( P > 0.05; Table 6 ) on the color values of L * and b * in milk among all groups during the entire storage period. However, light is one of the major environmental factors that affecting anthocyanin degradation ( 68 ). As a result, anthocyanin decreased significantly in response to increasing storage time ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, adding of anthocyanin did not impact ( P > 0.05; Table 6 ) on the color values of L * and b * in milk among all groups during the entire storage period. However, light is one of the major environmental factors that affecting anthocyanin degradation ( 68 ). As a result, anthocyanin decreased significantly in response to increasing storage time ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…Shading decreases the light intensity and increases the ratio of invisible light, including ultraviolet (UV) and IR radiation. Varying light quality has different effects on the quality of the fruits . Interestingly, the treatment of fruits with different qualities of light revealed that the red light does not affect berry size, whereas the far-red (FR) light had fewer effects .…”
Section: Resultsmentioning
confidence: 99%
“…Varying light quality has different effects on the quality of the fruits. 28 Interestingly, the treatment of fruits with different qualities of light revealed that the red light does not affect berry size, whereas the far-red (FR) light had fewer effects. 26 Therefore, the decrease in the ratio of IR radiation could cause a reduction in the weight.…”
Section: Ir− Affects Growth In Grapementioning
confidence: 99%
See 2 more Smart Citations